2015
DOI: 10.3184/175815515x14291701859483
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dietary Antioxidants on Broiler Oxidative Stress, Performance and Meat Quality: Science and Market

Abstract: Several production factors could exacerbate the biological formation of free radicals which, in turn, cause oxidative stress that impair the health, overall performance and meat quality of broiler chickens. Such factors could have a nutritional, pathological, physiological or environmental origin. The modern drive towards intensive commercial poultry production has elevated the exposure risk of broilers to these factors. In contrast, it has been demonstrated in many studies that dietary antioxidants could comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 88 publications
1
54
1
1
Order By: Relevance
“…To date, a definite explanation for the lack of effect by dietary supplementations on growth performance in HS birds remains unclear. Salami et al (2015) reported that several factors may be responsible for the efficacy of dietary supplementations in broiler chickens under HS, including dose and duration of supplementations, diets, age of birds and the level of stress. In this study, HS was associated with the reduced weight of active organs such as heart and intestine.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a definite explanation for the lack of effect by dietary supplementations on growth performance in HS birds remains unclear. Salami et al (2015) reported that several factors may be responsible for the efficacy of dietary supplementations in broiler chickens under HS, including dose and duration of supplementations, diets, age of birds and the level of stress. In this study, HS was associated with the reduced weight of active organs such as heart and intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Edens and Sefton (2016), Dalia et al, (2017) and Bakhshalinejad et al, (2018) obtained significantly lesser malondialdehyde concentration for Selenium supplemented group than negative control group. Significant decrease in TBARS value as influenced by selenium yeast than sodium selenite was reported by Sevcikova et al, (2006), Jokic et al, (2009), Hosseini-Mansoub (2011), Taulescu et al, (2011), Boiago et al, (2014), Chen et al, (2014, Delles et al, (2014), Salami et al, (2015) and Ravindran and Elliott (2017). Significantly decreased TBARS value was recorded at 0.15mg/kg selenium supplementation by Hooge (2007) while TBARS value noted for 0.3 mg/kg organic selenium was similar to control group.…”
Section: Antioxidant Status Of Birdsmentioning
confidence: 84%
“…Several factors which could be of nutritional, pathological, physiological or environmental origins could induce oxidative stress and impair the performance of chickens Salami, Guinguina, Agboola, Omede, Agbonlahor and Tayyab (Salami et al, 2015). Consequently, dietary antioxidants have been shown to counteract the negative effects of oxidative stress in poultry and extensive reviews have been provided for broiler chickens (Fellenberg and Speisky, 2006;Salami et al, 2015).…”
Section: Poultrymentioning
confidence: 99%
“…Consequently, dietary antioxidants have been shown to counteract the negative effects of oxidative stress in poultry and extensive reviews have been provided for broiler chickens (Fellenberg and Speisky, 2006;Salami et al, 2015). Table 2 depicts the recommended dietary antioxidant nutrients in poultry.…”
Section: Poultrymentioning
confidence: 99%
See 1 more Smart Citation